ANALYSIS OF EARLY MORTALITY BY BREAST CANCER IN BRAZIL AND GOIÁS FROM 2010 TO 2019 - Assunção, Silvaleide Ataides; Batista, Amanda Carlos de Lima; Amorim, Eduarda Duarte Mota; Amoroso, Giovanna Giulia de Carvalho; Reis, Rebeka Gyovana Rodrigues; Sousa, Lara Letícia Gaspar; Rahal, Rosemar Macedo Sousa (Mastology, 2021)
Introduction: Breast cancer is the second leading cause of death among women, affecting mainly the age group of 50–59 years, the age at which screening tests are recommended. However, it has shown a progressive incidence below 50 years. For this reason, the objective is to analyze the statistical data on early mortality from breast cancer up to 50 years, in view of possible losses in diagnosis and early management. Methodology: A descriptive epidemiological study, a retrospective of time series, using the data from the Mortality Information System (SIM) of the Health Surveillance Secretariat of the Ministry of Health (SVS/MS) in the period of 2010 and 2019, in Brazil and in the State of Goiás, was analyzed. Malignant neoplasms of death and women up to 50 years of age were included as causes of death. The data were compared and tabulated in Excel. Results: Deaths due to malignant breast cancer in Goiás, between 2010 and 2019, were 35 (20–29 years old), 306 (30–39 years old), and 766 (40–49 years old), equivalent to 26.2% of the total number of deaths in all age groups (1,107 cases). In Brazil, deaths were 1,149 (20–29 years old), 9,876 (30–39 years old), and 24,586 (40–49 years old), totaling 23.3%. Conclusion: According to the analysis, it is possible to point to an increase in deaths, especially for those aged 40–49 years. The lack of inclusion of women in this group interferes with the prognosis, since it makes the late diagnosis feasible and, in more advanced stages, causes less chances of cure. Possible adaptations and strategies for screening this public and coverage by public health systems must be considered.